2016
DOI: 10.1016/j.pharmthera.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targeting of hypoxia and hypoxia-inducible factors in cancer

Abstract: Insufficient tissue oxygenation, or hypoxia, contributes to tumor aggressiveness and has a profound impact on clinical outcomes in cancer patients. At decreased oxygen tensions, hypoxia-inducible factors (HIFs) 1 and 2 are stabilized and mediate a hypoxic response, primarily by acting as transcription factors. HIFs exert differential effects on tumor growth and affect important cancer hallmarks including cell proliferation, apoptosis, differentiation, vascularization/angiogenesis, genetic instability, tumor me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
434
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(446 citation statements)
references
References 261 publications
8
434
0
4
Order By: Relevance
“…HIF-2α is a type of HIFs involved in body response to oxygen level [51]. The expression of HIF-2α in various cancers has been recorded and detected by many studies [10,52]. HIF-2α expression may have a longer overall survival in hepatocellular carcinoma by Yang et al [53].. Bangoura et al reported that HIF-2α expression was correlated with a shortened overall survival of hepatocellular carcinoma [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HIF-2α is a type of HIFs involved in body response to oxygen level [51]. The expression of HIF-2α in various cancers has been recorded and detected by many studies [10,52]. HIF-2α expression may have a longer overall survival in hepatocellular carcinoma by Yang et al [53].. Bangoura et al reported that HIF-2α expression was correlated with a shortened overall survival of hepatocellular carcinoma [54].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia is a pathological hallmark that may be correlated with metabolism, the activation of cell signaling, angiogenesis, differentiation, necrosis or cell apoptosis, tumor development and aggressiveness, etc [10][11][12].. Additionally, tumor hypoxia can have an adverse impact on the prognosis of some cancers (i.e., invasive breast cancer or cervical cancer) and the efficacy of chemo-and radiotherapy [13,14]. Hypoxia-inducible factor-2α (HIF-2α), also named the endothelial PAS domain protein 1 (EPAS1), a member of the hypoxia-inducible factors (HIFs), is an essential marker, which mediates the transcriptional response to hypoxia stress [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIFs are transcription factors that control the expression of dozens of genes involved in angiogenic signalling, cell migration, energy metabolism, and other pathways (39).…”
Section: Cox-2 Specific Inhibitors Synergistically Enhance the Antitumentioning
confidence: 99%
“…In contrast, the knockdown of the AhR in MDA-MB-468 cells, an estrogen-independent cell line, did not affect cell proliferation (27). Hypoxia-inducible transcription is important for tumor progression (28). Since hypoxia-inducible factors (HIFs) also use ARNT as a partner factor, the AhRR may affect HIF signaling.…”
Section: Figmentioning
confidence: 99%